Sharpie® art workshop : techniques & ideas for transforming your world - Goodman, Timothy (Rockport Publishers, 2015)
In "Sharpie Art Workshop, " designer, artist, and art director Timothy Goodman explores Sharpie writing products, the materials and supplies that can be used to enhance or modify them, and the range of creative techniques and effects that can be achieved. Through a series of examples and exercises, Goodman demonstrates how to make different kinds of marks, patterns, and images on a variety of surfaces. Inspiring works by noted artists from all over the world who use Sharpie in interesting and innovative ways are also included.